2013
DOI: 10.1016/j.jacc.2013.07.079
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Chemoreceptor Ablation Improves Survival in Heart Failure

Abstract: Objectives We investigated whether selective ablation of the carotid body (CB) chemoreceptors improves cardiorespiratory control and survival during heart failure. Background Chronic heart failure (CHF) is a recognized health problem worldwide, and novel treatments are needed to better improve life quality and decrease mortality. Enhanced carotid chemoreflex drive from the CB is thought to contribute significantly to autonomic dysfunction, abnormal breathing patterns, and increased mortality in heart failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
133
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 170 publications
(136 citation statements)
references
References 34 publications
3
133
0
Order By: Relevance
“…7,12,19,23,24 Recently, new experimental evidence has shown that the CB is involved in several sympathetic-mediated diseases. 7,[47][48][49][50][51] The selective ablation of the CB reduced BP in spontaneous hypertensive rats, 50 reduced sympathetic hyperactivation, improved survival in heart failure experimental models , 30,52 and prevented the development of hypertension and insulin resistance in rats fed with a highfat diet. 51 Thus, it is possible that the ablation of the CB will improve cardiovascular control in OSA.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…7,12,19,23,24 Recently, new experimental evidence has shown that the CB is involved in several sympathetic-mediated diseases. 7,[47][48][49][50][51] The selective ablation of the CB reduced BP in spontaneous hypertensive rats, 50 reduced sympathetic hyperactivation, improved survival in heart failure experimental models , 30,52 and prevented the development of hypertension and insulin resistance in rats fed with a highfat diet. 51 Thus, it is possible that the ablation of the CB will improve cardiovascular control in OSA.…”
Section: Discussionmentioning
confidence: 99%
“…13,30 In addition, intravenous infusion of phenylephrine (25 µg/kg) and sodium nitroprusside (50 µg/kg) was used to fully determine the cardiac baroreflex function.…”
Section: Baroreflex Sensitivitymentioning
confidence: 99%
See 3 more Smart Citations